Exploring the needs for the development of organic reaction teaching model: experts’ collective opinion - Sabitu, Abdulmalik; Talib, Othman; Kamaruddin, Nurzatulshima; Abdul Rahman, Norizah (Secholian Publication, 2021)
This article reported the findings of a study carried out to investigate the need for developing an organic reaction mechanism teaching model. Qualitative data was obtained through a semi-structured interview among five chemistry subject matter experts to explore their opinion on the issues centered on the teaching and learning of organic reaction mechanisms. The interviews were interpreted and analyzed using thematic analysis. Five themes comprising of many codes and quotations were identified. The analysis of the findings shows that organic reaction mechanisms are one of the most significant and central concepts in science. However, students are faced with challenges in learning the concepts. Thus, the need for an alternative model of teaching the concept of organic reaction mechanisms.